Investigating Non-Tight Junction Functions of Claudin-7: Regulating Large Intestine Stem Cell Functions and Niche Maintenance, and Junctional Protein Nanoarchitecture - Naser, Amna (East Carolina University, 2022)
Edit this abstract.
Keywords: colorectal cancer; Claudin-7; tight junctions; IBD; Intestine, Large; Stem Cells; Claudins